2011
DOI: 10.1111/j.1540-8167.2010.01845.x
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Atrial Fibrillation at the Time of Cavotricuspid Isthmus Ablation in Patients With Atrial Flutter Without Documented Atrial Fibrillation Derives a Better Long-Term Benefit

Abstract: Ablation of AF at the time of CTI ablation results in a significantly better long-term freedom from arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 32 publications
2
32
1
Order By: Relevance
“…Our study confirmed the benefit of additional PVI in patients without documented AF as shown by Navarrete et al 15 They demonstrated that in patients with isolated AFL and no history of AF, a combination of CTI ablation and PVI reduced the rate of any tachyarrhythmias during follow-up compared with a standalone CTI ablation. 15 Although there was a comparable recurrence rate of AFL after CTI ablation, the recurrence rate after standalone PVI in our study is higher than that reported by Navarrete et al 15 in their CTI plus PVI group. However, as previously described, 21,22 implantable rhythm devices in our series allowed more detailed follow-up with identification of even asymptomatic arrhythmia episodes, possibly not recorded during 48-hour Holter monitoring.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Our study confirmed the benefit of additional PVI in patients without documented AF as shown by Navarrete et al 15 They demonstrated that in patients with isolated AFL and no history of AF, a combination of CTI ablation and PVI reduced the rate of any tachyarrhythmias during follow-up compared with a standalone CTI ablation. 15 Although there was a comparable recurrence rate of AFL after CTI ablation, the recurrence rate after standalone PVI in our study is higher than that reported by Navarrete et al 15 in their CTI plus PVI group. However, as previously described, 21,22 implantable rhythm devices in our series allowed more detailed follow-up with identification of even asymptomatic arrhythmia episodes, possibly not recorded during 48-hour Holter monitoring.…”
Section: Discussioncontrasting
confidence: 80%
“…7,15,26 Ellis et al 7 reported a high incidence of AF (up to 82%) after CTI ablation in patients with isolated AFL during mean follow-up time of 39 months. Wazni et al 26 demonstrated that in patients with both AF and AFL, PVI is sufficient to control both arrhythmias, although in the blanking period 55% of patients still had episodes of typical AFL and some patients had antiarrhythmic therapy or cardioversion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In my own experience and that of others, given sufficient time and electrocardiographic monitoring, “lone” AFL is a rare entity 3–9 . It is thus interesting to me that Navarrete et al were able to recruit 48 such patients at a single community hospital in a relatively brief span of time 1 . As intimated in their discussion, they would not be shocked if most of the cohort actually had both AFL and AF at the time of study enrollment.…”
Section: Editorial Commentmentioning
confidence: 92%
“…It must be kept in mind that recurrent RA flutter or tachycardia is a well-known complication of omitting a RA cavotricuspid isthmus line. 44 …”
Section: Extended La Lesion Setsmentioning
confidence: 99%